PENGARUH AKTIVITAS FISIK TERHADAP STRES OKSIDATIF - Candrawati, Susiana (Jurusan Kedokteran FK Unsoed, 2013)
At the moment, degenerative diseases have become the highest cause for morbidity and mortality in the world. One of the risk factors for degenerative disease to develop is low physical activity. Several theories revealed that there is a relationship between physical activity and oxidative stress, which is one of the basic pathogenesis of degenerative diseases. Physical activity have acute respon to increase the oxidative stress by several mechanism : hyperoxic injury in mitochondria, ischemia â reperfusion injury and inflammation. Besides that, reguler physical activity can cause chronic respon to decrease the oxidative stress by several mechanism : increasing proteasome activity & DNA repairing enzyme, decreasing DNA binding by redox-sensitive transcription factors (NF-ÎºB, AP-1, MAPK, dan CREB) and increasing endogenous antioxydant (superoxide dismutase / SOD & glutathione peroxidase / GSH-px). Therefore, it is important to perform reguler physical activity for the prevention of degenerative disease in the future